Pleurotus sajor-caju-Mediated Synthesis of Silver and Gold Nanoparticles Active against Colon Cancer Cell Lines: A New Era of Herbonanoceutics - Vivek K. Chaturvedi; Navneet Yadav; Neeraj K. Rai; Noura H. Abd Ellah; Raghvendra A. Bohara; Ibrahim F. Rehan; Najat Marraiki; Gaber El-Saber Batiha; Helal F. Hetta; M. P. Singh (Molecules, 2020)
Herbal medicines are widely used worldwide and much appreciated because of their fewer side effects and the ability to fight diseases at the root cause. Active ‘phyto’ ingredients require a scientific approach and a mechanism to distribute components at the target site for better therapeutic results. Nanotechnology, on the other hand, has created new hope for cancer treatment but is still far from being proven in clinical settings. This article combines a unique approach to synthesis with the use of Pleurotus sajor-caju, followed by microwave irritation of silver and gold nanoparticles that ensures the capping of the active phyto ingredient and further enhances the effects of nanomedicine to fight colon cancer, thus opening a new era of what we call herbonanoceutics. The article also compares the characteristics and properties of silver (Au) and gold (Ag) nanoparticles synthesized by an in house developed novel microwave-assisted rapid green synthesis method. The as-prepared Ag NPs and Au NPs were compared using ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and energy dispersive spectroscopy (EDS). Our comparative study revealed that both assemblies display face-centred cubic structures (FCCs) and are nanocrystalline in nature. The advantage of the approach was that the sizes of gold and silver were identical in range with a similar distribution pattern. This has helped us to study the activity against colon cancer cell line (HCT-116) without incoherence since size plays a key role in the application. More specifically, morphological changes, cell viability, the production of reactive oxygen species (ROS) and the fragmentation of DNA have been further reported to assess better the results obtained with the two metals. Our results suggest that the newly adopted synthesis method may ensure the dual benefits from phyto ingredients which further enhances the effectiveness of advanced nanomedicine.